2021
DOI: 10.3390/antibiotics10060691
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Hybrid Resistance and Virulence Plasmids Harboring New Delhi Metallo-β-Lactamase in Klebsiella pneumoniae in Russia

Abstract: The emergence of carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKp) is a new threat to healthcare. In this study, we analyzed nine CR-hvKp isolates of different sequence-types (ST) recovered from patients with nosocomial infections in two hospitals in Saint Petersburg. Whole-genome sequencing showed that eight of them harbored large mosaic plasmids carrying resistance to carbapenems and hypervirulence simultaneously, and four different types of hybrid plasmids were identified. BLAST analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
5
23
0
5
Order By: Relevance
“…“Currently, the mutation of D130G has been reported in NDM- 14, and kinetic analysis indicated that NDM-14 has greater carbapenem resistance with a higher affinity for imipenem and meropenem (Zou et al, 2015). Based on our research, there is no difference between NDM-1 and NDM-29 in terms of susceptibility to carbapenems, which is in accordance with the findings of Starkova et al ( 2021 ).”…”
supporting
confidence: 92%
See 2 more Smart Citations
“…“Currently, the mutation of D130G has been reported in NDM- 14, and kinetic analysis indicated that NDM-14 has greater carbapenem resistance with a higher affinity for imipenem and meropenem (Zou et al, 2015). Based on our research, there is no difference between NDM-1 and NDM-29 in terms of susceptibility to carbapenems, which is in accordance with the findings of Starkova et al ( 2021 ).”…”
supporting
confidence: 92%
“…Microbiol. 12:743981. doi: 10.3389/fmicb.2021.743981 In the original article, Starkova et al (2021) was not cited in the article. The citation has now been inserted in Introduction, paragraph 2 and Discussion, paragraph 3.…”
Section: A Corrigendum Onmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, susceptibility to the aminoglycosides and/or carbapenems was restored in these isolates ( Dataset S2 ). Finally, while the backbone of pSI0739-NDM was lost (event L) in isolate 752019, bla NDM-1 , carried on a Tn 125 -like transposon ( 21 , 22 ), integrated into the canonical pSI0739-ARMA-Vir plasmid, resulting in the de novo formation of hybrid plasmid pSI0646A-ARMA-Vir-NDM. Importantly, near-identical hybrid plasmids carrying determinants for virulence, carbapenem ( bla NDM ), and broad-spectrum aminoglycoside resistances are now emerging in isolates from various countries in both ST-147 and distinct convergent K. pneumoniae lineages ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, near-identical hybrid plasmids carrying determinants for virulence, carbapenem ( bla NDM ), and broad-spectrum aminoglycoside resistances are now emerging in isolates from various countries in both ST-147 and distinct convergent K. pneumoniae lineages ( SI Appendix , Fig. S3 ) ( 6 , 14 , 16 , 22 ).…”
Section: Resultsmentioning
confidence: 99%